To what extent does political rationality influence the contemporary patterns of violence and atrocity in postcolonial Sudan? - Maleswena, Tshepiso (My University, 2016)
Sudan is a state that has become synonymous with violent atrocities resulting from clashes between government forces and rebel groups The resulting death and displacement of scores of its civilians as a result of these clashes has captured the world’s attention and inspired an in depth analysis for the causes. This research report explores the impact that the political decision making by the postcolonial government in the form of rationality had on this circumstance and to what extent the governance procedure influenced the tensions that catapulted the state into violence. The North South, Muslim Christian dichotomy has been understood as the crux of the violence in Sudan, the reality however is much more complex and a variety of intricate factors converge to result in the spate of violent atrocities that has been suffered mostly by those who are not participants in the conflicts. Sudan’s history and its successive postcolonial governments are two factors that weigh greatly on these complexities, the process of political rationality in particular is central to this and as such forms the crux of the political decision making process by the governing structure. The analysis of political rationality as a concept provides an insight into the context that framed this process and is therefore vital to consider in trying to decipher and mitigate against the occurrence of further violent atrocities in Sudan specifically and generally in Africa as a whole.
A dissertation presented in partial fulfilment of the requirements for the Master of Arts Degree in Political Studies, Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2016
Keywords: Conflict management--Sudan; Violence--Sudan; Sudan--Politics and government